Using hyperpolarized 129Xe MRI to quantify regional gas transfer in idiopathic pulmonary fibrosis. Issue 1 (31st August 2017) - Wang, Jennifer M; Robertson, Scott H; Wang, Ziyi; He, Mu; Virgincar, Rohan S; Schrank, Geoffry M; Smigla, Rose Marie; O'Riordan, Thomas G; Sundy, John; Ebner, Lukas; Rackley, Craig R; McAdams, Page; et al.
Abstract : Background: Assessing functional impairment, therapeutic response and disease progression in patients with idiopathic pulmonary fibrosis (IPF) continues to be challenging. Hyperpolarized 129 Xe MRI can address this gap through its unique capability to image gas transfer three-dimensionally from airspaces to interstitial barrier tissues to red blood cells (RBCs). This must be validated by testing the degree to which it correlates with pulmonary function tests (PFTs) and CT scores, and its spatial distribution reflects known physiology and patterns of disease. Methods: 13 healthy individuals (33.6±15.7 years) and 12 patients with IPF (66.0±6.4 years) underwent 129 Xe MRI to generate three-dimensional quantitative maps depicting the 129 Xe ventilation distribution, its uptake in interstitial barrier tissues and its transfer to RBCs. For each map, mean values were correlated with PFTs and CT fibrosis scores, and their patterns were tested for the ability to depict functional gravitational gradients in healthy lung and to detect the known basal and peripheral predominance of disease in IPF. Results: 129 Xe MRI depicted functional impairment in patients with IPF, whose mean barrier uptake increased by 188% compared with the healthy reference population. 129 Xe MRI metrics correlated poorly and insignificantly with CT fibrosis scores but strongly with PFTs. Barrier uptake and RBC transfer both correlated significantly with diffusing capacity of the lungs for carbon monoxide (r=−0.75, p<0.01 and r=0.72, p<0.01), while their ratio (RBC/barrier) correlated most strongly (r=0.94, p<0.01). RBC transfer exhibited significant anterior-posterior gravitational gradients in healthy volunteers, but not in IPF, where it was significantly impaired in the basal (p=0.02) and subpleural (p<0.01) lung. Conclusions: Hyperpolarized 129 Xe MRI is a rapid and well-tolerated exam that provides region-specific quantification of interstitial barrier thickness and RBC transfer efficiency. With further development, it could become a robust tool for measuring disease progression and therapeutic response in patients with IPF, sensitively and non-invasively.